ChemInform Abstract: Distant C—H Activation/Functionalization: A New Horizon of Selectivity Beyond Proximity. Issue 51 (December 2015) - Sharma, Ritika; Thakur, Kavita; Kumar, Rakesh; Kumar, Inder; Sharma, Upendra
Abstract: Review: recent progress in remote C‐H activation, mechanistic understanding, and its aplication; 145 refs.